The influence of carbon-glass/epoxy hybrid composite under mode I fatigue loading: Physical-based characterization - Monticeli, Francisco M. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP] (Elsevier, 2022)
The aim of this study was to characterize the mechanical behavior of a carbon-glass/epoxy hybrid composite under cyclic loading and following physical-based interpretation for mode I delamination modeling. The hybrid composite shows a higher surface roughness due to a micro-change in the crack direction at the carbon/epoxy and glass/epoxy interfaces, with the simultaneous presence of both reinforcements along the entire fracture surface. The organosilane bond (at the glass fiber surface) extends the interphase chain, increasing the deformation interfacial area. In conclusion, the application of the maximal carbon-glass/epoxy interfacial number in hybrid laminates is a feasible option to increase delamination resistance, since a greater amount of energy needs to be overcome to enable damage formation, which results in longer fatigue life.
Keywords: Fatigue; Fractography; Hybrid composite; mode I delamination